Integrative analysis of circulating microRNAs and the placental transcriptome in recurrent pregnancy loss - Xu, Naixin; Zhou, Xuanyou; Shi, Weihui; Ye, Mujin; Cao, Xianling; Chen, Songchang; Xu, Chenming (Frontiers in Physiology, 2022)
Recurrent pregnancy loss (RPL) is a major type of pathological pregnancy that still lacks reliable early diagnosis and effective treatment. The placenta is critical to fetal development and pregnancy success, as it participates in critical processes such as early embryo implantation, vascular remodeling, and immunological tolerance. RPL is associated with abnormalities in the biological behavior of placental villous trophoblasts, resulting in aberrant placental function. MicroRNAs (miRNAs) are increasingly being recognized as essential regulators of placental development, as well as potential biomarkers. In this study, plasma miRNAs and placental messenger RNAs (mRNAs) from RPL patients and normal pregnant (NP) controls were sequenced and analyzed. Compared to those in NP controls, 108 circulating miRNAs and 1199 placental mRNAs were differentially expressed in RPL samples. A total of 140 overlapping genes (overlapping between plasma miRNA target genes and actual placental disorder genes) were identified, and functional enrichment analysis showed that these genes were mainly related to cell proliferation, angiogenesis and cell migration. The regulatory network between miRNAs, overlapping genes and downstream biological processes was analyzed by protein–protein interactions (PPIs) and Cytoscape. Moreover, the enriched mRNAs, which were predictive targets of the differentially expressed plasma miRNAs miR-766-5p, miR-1285-3p, and miR-520a-3p, were accordingly altered in the placenta. These results suggest that circulating miRNAs may be involved in the pathogenesis of RPL and are potential noninvasive biomarkers for RPL.